DEVELOPMENT OF MATHEMATICS INSTRUCTIONAL VIDEOS FOR 8TH GRADE STUDENTS - Arisa, Nadya; Alfiyah, Khomsyatun (CV. Doki Course and Training, 2025)
This study investigates the feasibility, practicality, and effectiveness of instructional mathematics videos supported by YouTube as an alternative learning medium for 8th-grade students. The research adopted the Research and Development (R&D) approach using the Borg and Gall model. Data were collected through expert validation, student questionnaires, and achievement tests. Instruments used included a validation rubric for media and material quality, a Likert-scale questionnaire for practicality, and a multiple-choice test to assess effectiveness. Effectiveness was categorized using a theoretical framework based on percentage classifications. The video scored 92% in media quality and 91% in material relevance, placing both in the “Very Valid” category. Small-group trials showed 88.8% practicality based on student feedback. Field tests indicated an effectiveness score of 72.9%, demonstrating improved student performance. The YouTube-based video is a valid, practical, and effective tool for mathematics instruction. It offers significant potential in engaging learners and enhancing conceptual understanding.